Muslim women’s contributions to society - Faris, Waleed Fekry (Centre for Muslims World Affairs, 2017)
Women because of their innate femininity, they are able to understand their fundamental role in family and in society as well, they’ve been able to apply the role through the approach of unity amongst the Ummah. Today it is expected for the younger generation to enhance their role in order to fulfil a much more effective approach than which have been applied in the past in regards to empowering our Muslim Ummah. We can say that today there are numerous advantages that befalls us in comparison to the past, spreading a message in today’s generation can easily be spread and heard, this aspect should be fully applied by our striving Ummah, as well as, creating a platform in a starting organization or by simply educating our youngsters on the importance of support, empowerment, unity and peace so they can develop a passion from a young age.